دراسة مقارنة لبعض المتغيرات الكينيتيكية لوصول الثقل الى اقصى ارتفاع بين المنتخبين العراقي والايراني في رفعة الخطف وعلاقتها بالانجاز - علاوي, معد مانع; صبري, ليث اسماعيل; محمد, عبدالله حمد (Sulaimani Journal for Humanities, 2018)
Summery The research aims to identi8r the effect of resistance ballistic exercises in a contrasting manner on some physical abilities (strength, fast strength and digital achievement level of 100m running).I assumed existence of positive impact in the Research variables ,applying the research on six samples representing players of peshmarga Suleimanyah clubs. The research concluded that the ballistic resistance exercises which is carried out in contrasting method with polymeric exercises inside the groups of exercising program was effective in the research variables. The study summarized that usage of contrasting between both methods in regards with equity of the exercise abilities.